PENGARUH MODEL MAKE A MATCH BERBANTU MEDIA FLASH CARD MAPU TERHADAP HOTS IPAS SISWA KELAS V SD - Silvi Yunita Wulandari; Yulina Ismiyanti (Universitas Negeri Medan, 2026)
The Higher Order Thinking Skills (HOTS) of elementary school students still need to be improved because the learning tends to be teacher-centered and does not actively involve the students. This study aims to determine the effect of the Make a Match learning model assisted by MAPU Flash Card media on HOTS abilities in fifth-grade elementary school IPAS learning. The research uses a quantitative approach with a One Group Pretest-Posttest design involving 24 fifth-grade students. Data were obtained thru descriptive tests before and after the treatment, and then analyzed using validity, reliability, normality tests, and the Paired Sample T-Test. The research results show an increase in the average score from 71.57 in the pretest to 85.42 in the posttest with a significance value < 0.05. Based on these results, it can be concluded that the Make a Match learning model assisted by MAPU Flash Card media has a positive effect on improving the HOTS IPAS abilities of fifth-grade elementary school students.